PERSPEKTIF MAHASISWA TERHADAP PEMBELAJARAN AKIDAH AKHLAK DI JURUSAN PENDIDIKAN AGAMA ISLAM FAKULTAS TARBIYAH DAN KEGURUAN UIN ALAUDDIN MAKASSAR - Darwis, Riska; Amri, Muhammad; Moshiba, Risna; ., Baharuddin (Universitas Islam Negeri Alauddin Makassar, 2021)
Student perspectives on morality learning strategies in the Islamic Education Department at the Tarbiyah and Teacher Training Faculty are good and student perspectives on moral learning media in the Islamic Religious Education Department at the Tarbiyah and Teacher Training Faculty are also good, where this media is an intermediary, information channel or conveyor. the message to smooth the learning process while the student's perspective on the akidah akhlak learning model in the Islamic Religious Education Department at the Tarbiyah and Teacher Training Faculty is already good. Basically, it is a form of learning that is illustrated from beginning to end which is specially presented by educators. One of the models applied by the lecturer is Contextual Teacing and Learning (CTL), the PAIKEM model (Parsipative, Active, Innovative, Creative, Effective and Fun) and a cooperative model that can help students to facilitate the teaching and learning process in the Islamic Education Department of the Tarbiyah Faculty and Teachers of UIN Alauddin Makassar